Graphical user interface development for streamline testing of concentrator cards - Weinschenk, Sedrick William (Kansas State University, 2022)
The Large Hadron Collider (LHC) at CERN has provided vital information to aid in understanding how particles interact. One of the latest achievements was the discovery of the Higgs boson in 2012 by the CMS and ATLAS collaborations at CERN. The Higgs boson was the missing piece of the standard model (SM) of particle physics. However, there are still phenomena that are not explained by the SM that lead researchers to believe there are particles predicted by new theories beyond the SM. Some of these particles can be produced in rare events at the LHC. The upgrade of the LHC for high luminosity operations, so called High Luminosity-Large Hadron Collider (HL-LHC), will allow interactions at higher energy and higher rate. This will result in producing more events of these rare processes and particles, and hopefully, lead to discoveries beyond the SM. The MIP timing detector (MTD) is one of the novel installments in the CMS detector for the HL-LHC operation phase that will allow for precision timing. Concentrator cards (CCs) will be placed in the MTD to communicate between the detector and the data acquisition system by sending timing signals between them. Hundreds of CCs will be assembled and tested at Kansas State University. This thesis discusses the development of a graphical user interface (GUI) that will improve the CC testing process. It will discuss the structure and application of the different modes of the testing process, along with future developments.
Keywords: Graphical user interface; Concentrator card